Integrated approach in determining priority environmental issues in Medan City North Sumatra Province. (December 2019) - Rahmawaty,; Perdinan,; Dewi, N W S P; Kurniawan, H
Abstract: Medan City is one of the largest cities in Indonesia. Geographically, Medan City is located between coordinates 2° 27' – 2° 47' North Latitude and 98 35' – 98° 44' East Longitude. The regional government of Medan is currently carrying out various efforts to overcome environmental problems in Medan City. This study aimed to analyze priority issues that need to be addressed in Medan City. This study was conducted from May to October 2018. The research consisted of several stages of activities, namely: desk review, public consultation with stakeholders, and data analysis. The desk review was conducted to examine various regulations and documents related to the management of Medan's natural and environmental resources and the environmental problems of Medan City. Public consultation with stakeholders was carried out with focus group discussions (FGD), filling out online questionnaires, and auditing with stakeholders. Priority issues were analyzed using the Driving Force, Pressure, State, Impact and Response (DPSIR) approach. Based on an integrated approach, the main issues obtained were the main problems in Medan, namely: Garbage, Water quality and quantity, and Air quality. The three main issues require rapid handling to prevent environmental damage in Medan City.